2012
DOI: 10.2340/00015555-1319
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting Diodes at 830 and 850 nm Inhibit Melanin Synthesis In vitro

Abstract: Treatment of hyperpigmentation remains a challenge. Because of the positive effects of low-energy Nd:YAG lasers on the treatment of melasma, it is suggested that laser-like light-emitting diodes (LEDs) can potentially ameliorate hyperpigmentation. We evaluated the effect of seven different LED wavelengths on melanogenesis. LED irradiation at 830 nm (dose-dependent, from 1 to 20 J/cm2) and 850 nm (1 J/cm2) significantly reduced melanin production and tyrosinase expression, not only in a normal human melanocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Subsequently, the melanin content was determined by the sodium hydroxide lytic cell method (Figure 3c). 47 The KPV-Lipo group possesses approximately 1.48-fold greater melanin synthesis rate than that of Lipo group (P < 0.05), while no significant difference was found between free KPV, free KPV + Lipo and KPV-Lipo group. Furthermore, the expression levels of TYR, tyrosinase-related protein 1 (TRP1), and tyrosinase-related protein 2 (TRP2) were measured by Western blotting.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Subsequently, the melanin content was determined by the sodium hydroxide lytic cell method (Figure 3c). 47 The KPV-Lipo group possesses approximately 1.48-fold greater melanin synthesis rate than that of Lipo group (P < 0.05), while no significant difference was found between free KPV, free KPV + Lipo and KPV-Lipo group. Furthermore, the expression levels of TYR, tyrosinase-related protein 1 (TRP1), and tyrosinase-related protein 2 (TRP2) were measured by Western blotting.…”
Section: Resultsmentioning
confidence: 78%
“…The KPV-Lipo and KPV+Lipo groups both showed 1.37-fold greater TYR activity than the Lipo group (Figure b). Subsequently, the melanin content was determined by the sodium hydroxide lytic cell method (Figure c) . The KPV-Lipo group possesses approximately 1.48-fold greater melanin synthesis rate than that of Lipo group ( P < 0.05), while no significant difference was found between free KPV, free KPV + Lipo and KPV-Lipo group.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using 630-nm and 830-nm LEDs have shown that LED treatment led to the reduction of wrinkles around the eyes and skin pigmentation and improved skin texture [ 10 , 11 , 12 ]. Kim confirmed that irradiation by 830-nm and 850-nm LEDs reduced melanin production and tyrosinase expression in normal human melanin cells [ 13 ]. Furthermore, some studies have reported that UV-induced damage was prevented when human fibroblasts were irradiated with near-infrared light [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 87%
“…Contrary to the clinical study above, near IR light has been shown to inhibit melanin synthesis in vitro . In this in vitro study, the effect of seven different LED wavelengths upon melanogenesis was studied using cultured human melanocytes (415 nm (54.8 mW cm −2 ), 530 nm (15.8 mW cm −2 ), 630 nm (22.2 mW cm −2 ), 660 nm (17.1 mW cm −2 ), 830 nm (96 mW cm −2 ), 850 nm (114 mW cm −2 ) and 940 nm (55.5 mW cm −2 ).…”
Section: Skin Pigmentation and Lighteningmentioning
confidence: 95%